Education and training territory: the case of the april 8 settlement Project in JardimAlegre/PR (Research, Society and Development, 2020)
School education is present in all segments of society and is considered important for everyone. For settlers it is essential that their children have access to this training and that it is used as a form of emancipation in the face of social inequalities. This text aims to discuss institutional education and the formation of the Landless Rural Workers Movement (MST) as a territoriality and producer of the territory of the Settlement Project Oito de Abril de JardimAlegre. For the development of the discussion around the formation and institutional education of the settlement, interviews were conducted with settlement leaders and teachers at the Colégio Rural Estadual José Martí and with the Municipal Secretary of Education of the municipality of JardimAlegre, in the state of Paraná, south of Brazil..